2017
DOI: 10.3762/bjnano.8.181
|View full text |Cite
|
Sign up to set email alerts
|

Non-intuitive clustering of 9,10-phenanthrenequinone on Au(111)

Abstract: The direct injection of a 9,10-phenanthrenequinone in tetrahydrofuran solution on a Au(111) substrate in high vacuum results in the formation of metastable clusters with a non-intuitive structure. Metastable, rectangular tetramers of this molecule form in which the net molecular dipoles all orient toward the center of the cluster. This structure does not allow for additional hydrogen bonding and thus the origin of its metastability is not clear. We compare this feature to other structures observed on this surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We have shown that these nonequilibrium conditions can produce metastable 2D structures. [33][34][35]43 According to Ostwald's rule, 44 the least stable species will precipitate out first, potentially becoming kinetically locked on the surface. Although there are examples of solvent-controlled 2D polymorphism at the liquid−solid interface, 45−47 neither the phthalimide tetramer networks nor the isatin pentamers were solvent-dependent species (Figure S4).…”
Section: ■ Methodsmentioning
confidence: 99%
“…We have shown that these nonequilibrium conditions can produce metastable 2D structures. [33][34][35]43 According to Ostwald's rule, 44 the least stable species will precipitate out first, potentially becoming kinetically locked on the surface. Although there are examples of solvent-controlled 2D polymorphism at the liquid−solid interface, 45−47 neither the phthalimide tetramer networks nor the isatin pentamers were solvent-dependent species (Figure S4).…”
Section: ■ Methodsmentioning
confidence: 99%
“…As one of the most abundant quinones found in DEPs [ 43 ], when inhaled, 9,10-PQ can be generated from phenanthrene by P-450s as below pathway [ 37 ]. Phenanthrene is one of major PAHs present in the air pollution [ 37 52 ].…”
Section: 910-phenanthrenequinone Is One Of the Major Components Omentioning
confidence: 99%
“…As a redox-active quinone in diesel exhausts, 9,10-PQ has been shown to generate ROS ( Figure 2 ) via its redox cycling resulting in its toxicity [ 37 52 , 57 , 62 , 63 , 67 , 71 88 ] in vitro and in vivo. 9,10-PQ can accept an electron to produce the semiquinone form of 9,10-PQ [ 70 ].…”
Section: Redox Cycling Of 910-pq In the Generation Of Reactive Oxmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show the endocrine system interference, cytotoxicity, genetic toxicity, and carcinogenicity of oxy-PAHs. One type of oxy-PAH, 9,10-phenanthraquinone (9,10-PQ), induces the production of reactive oxygen species (ROS) (9,17,31,46,67) and causes apoptotic cell death at submicromolar concentrations (49). The average concentration of 9,10-PQ in airborne particulates is 0.287 Ϯ 0.128 ppm (88).…”
Section: Introductionmentioning
confidence: 99%